Sports balls as potential SARS-CoV-2 transmission vectors - Pelisser, M.; Thompson, J.; Majra, D.; Youhanna, S.; Stebbing, J.; Davies, P. (Public Health in Practice, 2020)
Objects passed from one player to another have not been assessed for their ability to transmit severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We found that the surface of sport balls, notably a football, tennisball, golf ball, and cricket ball could not harbour inactivated virus when it was swabbed onto the surface, even for 30 s. However, when high concentrations of 5000 dC/mL and 10,000 dC/mL are directly pipetted onto the balls,it could be detected after for short time periods. Sports objects can only harbour inactivated SARS-CoV-2 underspecific, directly transferred conditions, but wiping with a dry tissue or moist `baby wipe` or dropping and rolling the balls removes all detectable viral traces. This has helpful implications to sporting events.